Perancangan Lapis Pondasi Agregat Tanpa Penutup Aspal Pada Gradasi Batas Tengah Dengan Menggunakan Clay Stone - Ahmad Norhadi; H. Muhammad Fauzi; Akhmad Marzuki; Zuraida Zuraida (P3M Politeknik Negeri Banjarmasin, 2018)
â€œLapis Pondasi Agregat tanpa penutup aspalâ€ is a strong layer structure because it receives a direct load of vehicles above the surface. In general, the making of access roads for mining sites does not use pavement with asphalt. One of the materials for mining pavement generally uses the mine's surface excavation using a clay stone as an addition to a mixture or filler for the aggregate layer structure. Clay stone is a sedimentary rock that is strong if it is in the soil and will become soft when submerged in water. â€œLapis Pondasi Agregat tanpa penutup aspalâ€ is dominated by fine particles which is a maximum diameter of 19 mm making it difficult to adjust the gradation composition. So to get the ideal gradation of â€œLapis Pondasi Agregat tanpa penutup aspalâ€ composition, it is necessary to do Research on â€œLapis Pondasi Agregat tanpa penutup aspalâ€ on Middle Border Gradations Using Clay Stone